Synthesis and Biological Activities of Some Arylazopyrazoles - SHARMA, K.P.; K. SHARMA, HARENDRA (Asian Journal of Chemistry, 2010)
Reaction of different diazonium chlorides with acetylace-tone afford 2,4-diketo-3-(unsubstituted/substituted phenylazo) pentanes (1), which on treatment with 2-(2,5-dichloroanilido) aceto hydrazide (2) in acetic acid medium resulted in the formation of 1-(2,5-dichloroanilinomalonyl)-3,5-dimethyl-4-(unsubstituted/substituted phenylazo) pyrazoles (3). Antibacterial and antifungal activities of 3 were also determined.